Issue Information TOC. Issue 1 (18th March 2019) - Unknown
Abstract : Cover : In Eller et al. (https://doi.org/10.1002/cpcy.54 ), Hierarchical gates to evaluate fluorescent cells. Gates are applied identically to all samples. The P1 gate outlines the uniform population of HeLa cells for evaluation (typically >75% of total events). Under these specific conditions, events in the red region represent cellular debris or mechanically disrupted cells; if >50% of events are in this region it indicates an overall unhealthy sample. From the P1/cell population, single cells are identified by the P2 gate using their size distribution (typically >90% of P1). The P3/fluorescent population is derived from the P2/single cell population. The P3 fluorescent cell population is defined by a gate that excludes non‐fluorescent cells in the untransfected sample (gray) and includes transfected cells (green, typically >50% of P2). There should be 10, 000 events in P3 for an accurate evaluation. To calibrate the sensor in cells, an additional gate is required to identify the permeabilized and equilibrated cells. This P4 gate (typically >85% of P3) is derived from uniform, single cells in P2, and is delineated by equilibrated intracellular propidium iodide (PI). Fluorescence is then evaluated in P5, which is derived from P4. In this example, a gray density contour plot in the lower left quadrant represents cells that do no express either sensor or cpVenus. Cells that express either sensor or cpVenus populate P5, and the fluorescence of the populations treated with either equilibrated buffer (red) or 500 μM NAD+ (indigo) are overlaid. Data was collected on a BD Fortessa flow cytometer and analyzed on FlowJo V10 software. See e54.